Muscle Hypertrophy Response to Range of Motion in Strength Training: A Novel Approach to Understanding the Findings. Issue 2 (19th April 2023) - Ottinger, Charlie R.; Sharp, Matthew H.; Stefan, Matthew W.; Gheith, Raad H.; de la Espriella, Fernando; Wilson, Jacob M.
ABSTRACT: One resistance training variable that may be altered to achieve desired outcomes is the range of motion used in training. Generally, the strength and conditioning field has accepted that using a greater range of motion in strength training exercises results in more substantial muscle hypertrophy outcomes. However, this theory has proved to be inconsistently supported in the literature, and to date, no sufficient explanation exists to explain this phenomenon. This review article seeks to outline a novel approach for potentially describing the disparities seen in range of motion research with respect to hypertrophy outcomes by applying the unique length-tension curve of each muscle being examined. As will be discussed in the review, virtually all the results from range of motion studies in various muscles have corresponded to each muscle's length-tension curve; muscles that are active on the descending limb of the curve appear to garner greater hypertrophy from using larger ranges of motion. Conversely, muscles that are not active on the descending limb exhibit similar adaptations despite alterations in range of motion. A novel hypothesis for applying this information to resistance training programs will be presented and discussed.